Removal performance and dissolved organic matter biodegradation characteristics in advection ecological permeable dam reactor - Yuan, Donghai (Environmental technology, 2023)
In this present study, an advection ecological permeable dam (AEPD) based on a biofilm reactor was established to investigate pollution control performance and dissolved organic matter (DOM) bio-degradation. The AEPD achieved optimal efficiency-chemical oxygen demand, 6-53 mg/L; total nitrogen concentration, 1.47-6.89 mg/L; total phosphorus concentration, 0.53-3.93 mg/L, and increases in values for ultraviolet-visible parameters-SUVA254, from 0.392 to 0.673-1.438; E4/E6, from 1.09 to 1.11-1.26; A240-400, from 12.06 to 13.09-19.95; and A253-203, from 0.03 to 0.04-0.23. This showed that DOM degradation promoted its humification, aromatisation, and unsaturation as well as increased the number of polar functional groups in the organic aromatic rings of DOM. Synchronous fluorescence and parallel factor analyses indicated that AEPD could effectively degrade tyrosine-like and tryptophan-like compounds, which showed the most significant decrease in fluorescence intensity. Additionally, AEPD displayed some stable dominant bacterial genera (e.g. Proteobacteria_unclassified, Bacteroidetes_unclassified, Gemmobacter, Pseudofulvimonas, Flavobacterium, Pseudomonas, and Nitrospira), although their relative abundance differed under variable hydraulic loading rates. This research provided further technical support for the application of AEPD in the treatment of water environment pollution